Health education in primary school textbooks in iran in school year 2010-2011. - Reza Kazemian; Hadi Ghasemi; Taraneh Movahhed; Ali Kazemian (Tehran University of Medical Sciences, 2014)
Health education in schools is one of the most effective ways of promoting health in a society. Studies have shown the effectiveness of health interventions aimed at improving students' knowledge, attitude, and behaviors about health issues. The aim of this study was to evaluate health issues in primary school textbooks in Iran.In school year 2010-2011, the contents of all primary school textbooks in Iran were assessed in accordance to their health-related teachings. Health lessons of these 27 textbooks in the form of picture and text were retrieved and analyzed using content analysis method.In total, 502 health-related lessons were found. The textbooks of the third grade contained the highest (144) and those of the fourth grade had the lowest (26) number of health lessons. Among health-related issues, the largest number (87) of lessons were about personal hygiene, while prevention of high risk behaviors comprised the least number (8). Some important health issues such as nutrition, oral health, and prevention of high-risk behaviors were not adequately discussed in the textbooks.The potential of primary school textbooks in delivering health messages has been neglected in Iran. Taking the critical importance of school ages into account, incorporating health issues in textbooks should be more strongly emphasized.